PENDAMPINGAN PENGEMBANGAN SISTIM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) DI DESTINASI WISATA TAMAN TEBING BREKSI, D.I. YOGYAKARTA - Helfi Agustin; Machfudz Eko Arianto; Muchamad Rifai (Universitas Muhammadiyah Tapanuli Selatan, 2021)
In general, law enforcement on occupational safety and health (OSH) has not been well implemented in the non-formal sector. One of them is community-based tourism. The obstacles include the absence or not yet functioning of OSH institutions. In fact, the tourism industry can easily sink due to tourists' discomfort and insecurity from disease outbreaks, natural disasters, and accidents. The purpose of community service is to assist in developing the OSH Management System at Tebing Breksi. This community service will contribute to the internalization of everyone's OSH culture at Tebing Breksi that will impact the tourism sector's recovery after the Covid-19 pandemic. The implementation method is through the advocacy approach, outreach, and assistance of the OSH program. The result of community service is top management policies in OSH commitment, organizational structure (the committee in charge of OSH), and hazard identification training as a requirement for making SOPs. The sustainability of the OSH management system will encourage the realization of an OSH culture for every worker in tourism services.